SIGNIFICANT LEVELS OF STEEL SLAG CONCRETE PRODUCED WITH VARYING WATER CEMENT RATIOS - SOLOMON IDOWU ADEDOKUN; MUKAILA ABIOLA ANIFOWOSE; SAMSON OLALEKAN ODEYEMI; JOHNSON ROTIMI OLUREMI (Journal of Engineering Studies and Research)
This study investigated the significance of steel slag concrete created with varying water cement ratios. Steel slag from Prism Nigeria Limited was used to replace granite (at 0, 40, 50 and 60 %) in concrete. Properties of this modified concrete were examined and its results were exposed to measurable test utilizing Analysis of Variance (ANOVA). The outcome indicated that the compressive and flexural qualities of the concrete increased with increased in slag content but consistently decreased as the water-cement ratios increased. The p-values of the ANOVA test for the models term are significant because they are less than 0.05.